Female rural-urban migrants and online marketplaces in emerging economies: Evidence from Thailand and Viet Nam - Trung Thanh Nguyen; Manh Hung Do (Asian Development Bank Institute (ADBI), 2022)
This research aimed to examine the factors affecting the participation of female rural-urban migrants in online marketplaces, and the welfare gains and their distribution from their participation. Our analysis was based on a unique data set of rural households, villages, and rural-urban migrants in Thailand and Viet Nam. Online market participation is classified into three activities: financial transaction; trading; and business. We accounted for the endogeneity issue of online market participation in welfare impact assessment by using an instrumental variable approach. Our results show that the participation has a positive effect on the consumption of female migrants only when they participate in the complete bundle of online market activities. In addition, we also find that the poor benefit insignificantly from online marketplaces. This raises a concern regarding increasing welfare inequality and suggests that the poor should be supported in order not to be left behind.
Keywords: O18; R11; I30; 330; impact; welfare; poverty; endogenous; heterogeneity; instrumental variable